Própolis e geoprópolis verde do semiárido do brasil: Caracterização química, origem botânica e atividade antioxidante - Ferreira, Joselena Mendonça (Universidade Federal Rural do Semi-Árido, 2019)
Studies to identify compounds in propolis have been expanded in recent years in northeast Brazil. However, up to now knowledge about the description of propolis and geopropolis and a geopropolis, both in green color, produced in this region. Samples of propolis and geopropolis were clorrected in the stato of Rio Grande do Norte, Brazil. Young and ripe shoot of jurema-preta (Mimosa tenuiflora) were also collected, as suspected to be the main botacinal source of these samples. Propolis, geopropolis and shoot samples were submited to ethanoilic extraction in Soxhlet for 6 hours. Extracts of propolis and geopropolis samples were used to evaluate basic parameters for commercialization. In sequence, the extracts were analyzed in HPLC-DAD-MS/MS, for identification and qualification of theis respective phnolic compounds. Finally, the samples underwent two testes to identify the botanical origin: 1) Comparison of chemical compounds in M. tenuiflora shoot, propolis and geopropolis extracts. 2) Microscopic comparison of M. tenuiflora plant tissues with those found in propolis and geopropolis samples. According to current legislation, propolis and geopropolis samples obtained acceptable evaluation for commercialization, presenting high antioxidant activity. The analysis showed above-normal total flavonoid levels for Brazilian propolis (117 and 98.5 g/kg, for propolis and geopropolis respectively). Eighteen prnolic compounds were found in the ethanolic extractos of M. tenuiflora shoot and propolis, mostly flavonols and chalcones. Ten of 18 were found in green geopropolis extract, plus 6 differente compounds. In microscopic analyses sereval shoot of M. tenuiflora were found, both in propolis and in geopropolis. It was also possible to describe some epidermal structures of the plant and to evaluate some of its characteristics. This study concluded that green propolis and geopropolis of Caating semiarid biome are qualified for comercialization, with analytical parameters according to inticated legislation, and M. tenuiflora is the botanical source of green propolis and geopropolis of this semiarid biome. This study will guide future researches aiming to optimize beekeeping in Caating Brazilian semiarid and protect important endemic plant species as M. tenuiflora
Keywords: Resina das abelhas; Mimosa tenuiflora; Compostos fenólicos; Apicultura do semiárido; Caatinga; Resins of bees; Mimosa tenuiflora; Phenolic compounds; CIENCIAS AGRARIAS::MEDICINA VETERINARIA